Desain Bahan Ajar Berbasis Project Based Learning dengan Ciri Kearifan Lokal untuk Melatih Keterampilan Berpikir Kreatif pada Era Society 5.0 - Perdana, Dayu Rika; Izzatika, Amrina; Hariyanto, Hariyanto; Apriliyani, Resti; Nurwahidin, Muhammad (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
This research aims to explore the effectiveness of Project-Based Learning (PBL) based learning material design that utilizes local wisdom in fostering creative thinking abilities during Society 5.0. This research uses a qualitative method with a case study design. Data was collected through participant observation, in-depth interviews with students and lecturers, document analysis of teaching materials, and documentation studies. The research results show that the design of PBL-based teaching materials with the integration of local wisdom is effective in increasing student involvement in learning and training their creative thinking skills. The project-based learning process encourages collaboration between students and intense interaction with local communities, while the integration of local wisdom makes learning more relevant and contextual for students. The implications of this research show the importance of developing learning design skills for lecturers, active involvement of students in learning, and the need for further research to explore the effectiveness of this approach in a broader educational context. It is hoped that the results of this research can contribute to improving the quality of education in the Society 5.0 era.